2021
DOI: 10.1007/s00253-021-11731-y
|View full text |Cite
|
Sign up to set email alerts
|

Hyperosmolarity adversely impacts recombinant protein synthesis by Yarrowia lipolytica—molecular background revealed by quantitative proteomics

Abstract: In this research, we were interested in answering a question whether subjecting a Yarrowia lipolytica strain overproducing a recombinant secretory protein (rs-Prot) to pre-optimized stress factors may enhance synthesis of the rs-Prot. Increased osmolarity (3 Osm kg−1) was the primary stress factor implemented alone or in combination with decreased temperature (20 °C), known to promote synthesis of rs-Prots. The treatments were executed in batch bioreactor cultures, and the cellular response was studied in term… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
16
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 16 publications
(17 citation statements)
references
References 73 publications
1
16
0
Order By: Relevance
“…Abundance of necessary transcription factors, polymerase elements, nucleotides and others were secured by higher rate of the nutrients consumption ( Figure 1 , Table 1 ) that could be obtained at a higher oxygen transfer capacity (i.e., kLa 110 h −1 ). Similar results were obtained by [ 22 ], where the Authors observed lower expression levels of a native lipase in Y. lipolytica cultured under oxygen deficiency. In addition, the critical role of OA for the expression level of heterologous genes in Y. lipolytica is further highlighted by the lack of significant impact of the medium pH on the heterologous gene transcription level ( Figure 2 ).…”
Section: Discussionsupporting
confidence: 90%
See 3 more Smart Citations
“…Abundance of necessary transcription factors, polymerase elements, nucleotides and others were secured by higher rate of the nutrients consumption ( Figure 1 , Table 1 ) that could be obtained at a higher oxygen transfer capacity (i.e., kLa 110 h −1 ). Similar results were obtained by [ 22 ], where the Authors observed lower expression levels of a native lipase in Y. lipolytica cultured under oxygen deficiency. In addition, the critical role of OA for the expression level of heterologous genes in Y. lipolytica is further highlighted by the lack of significant impact of the medium pH on the heterologous gene transcription level ( Figure 2 ).…”
Section: Discussionsupporting
confidence: 90%
“…The model strains were subjected to a series of batch cultivations with implemented stress factors, namely acidic pH and limited OA, applied alone or in combination. Although Y. lipolytica is known to grow well in a wide pH range without relevant impact on growth [ 17 , 28 , 29 , 33 , 34 ], oxygen deficiency is a strong limiting factor for this species [ 18 , 19 , 22 , 28 ]. Combination of the extrinsic stress factors and metabolic load in relation to growth, morphology and rs-Prots synthesis has not been studied previously in Y. lipolytica .…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Downregulation of membrane potassium channel (A00847p) hallmarks active adjustment of ions equilibrium. Another downregulated protein was sphingolipid long-chain base-responsive protein Lsp1 (C11341p), which together with Pil1 (identified as osmo-stress responsive in Y. lipolytica (Kubiak-Szymendera et al 2021b )) are known to act in close proximity of cell membrane, and to be involved in the regulation of cell growth, heat stress responses, endocytosis, wall synthesis and repair, as well as repolarization of the actin cytoskeleton in response to stresses. Further insight into the Y. lipolytica osmo-proteome was provided in a recent study by Kubiak-Szymendera et al ( 2021b ).…”
Section: External Stress Factorsmentioning
confidence: 99%